Morbidite Et Mortalite Dans Un Service D’hepato- Gastroenterologie En Milieu Tropical - A. Bagny; O. Bouglouga; LM. Lawson-Ananissoh; YR. El Hadji; LY. Kaaga; D. Redah (European Scientific Journal, ESJ, 2016)
Aims: This study aims at studying the key parameters of our patients such as morbidity and mortality. Knowing these parameters will enable to objectively assess the epidemiological profile of the patients, the terms of their care taking as well as the efficiency and the profitability of our service. Method: This is a descriptive retrospective study over a year (from January 1st to December 31st, 2015). We included in the study patients of both sexes hospitalized and examined in the unit. Results: The hospitalization rate was 33.5 %. It was about 564 men (57.3 %) and 420 women (42.7 %) accounting for a sex ratio of 1.3. The patients’ average age was 48.1 years old (extremes: 22-80 years old). Chronic liver diseases were the first main cause of hospitalization with 43 % of cases. We noticed 26% of cirrhosis and 17% of hepatocellular carcinoma. The average hospital stay was 6.48 ± 5.45 days with some extremes of 1 and 57 days. The Co-morbidities found were mostly hypertension (10.8 %), HIV (6.1 %), and diabetes (1.3 %). The overall mortality rate was 14.8 % and was higher in men (p = 0.006). The specific mortality was higher in cirrhotic patients (6.6 %) and those with HCC (4.7 %). The highest lethally rates were those of colon cancers (100%) and pancreas (42.8 %). Conclusion: This study has enabled us to inventory the major causes of morbidity and mortality in our department. Mortality is influenced by gender, co-morbidities and tobacco. Digestive cancers are the most lethal diseases in our department.